(x - 2) : 2 x 3 = 6
(x-2) :2 =6:3
(x-2) :2 =2
(x-2) =2x2
x-2 =4
x =4+2
x =6
( x -2 ) : 2 x 3 = 6
⇔ ( x - 2 ) : 2 = 6 : 3
⇔ ( x - 2 ) : 2 = 2
⇔ ( x - 2 ) = 2 x 2
⇔ x - 2 = 4
⇔ x = 4 - 2
⇔ x = 2
Vậy x = 2
( x - 2 ) : 2 x 3 = 6 .
( x - 2 ) : 2 = 6 : 3 .
( x - 2 ) : 2 = 2 .
x - 2 = 2 x 2 .
x - 2 = 4 .
x = 4 + 2 .
x = 6 .
Vậy x = 6 .
( x - 2 ) : 2 x 3 = 6
( x - 2 ) : 2 = 6 : 3
( x - 2 ) : 2 = 2
x - 2 = 2 x 2
x - 2 = 4
x = 4 + 2
x = 6
x = 6
( x - 2 ) : 2 x 3 = 6
( x - 2 ) : 2 = 6 : 3
( x - 2 ) : 2 = 2
( x - 2 ) = 2 x 2
( x - 2 ) = 4
x = 4 + 2
x = 6